OPEN ACCESS RESOURCES: CHALLENGES AND OPPORTUNITIES FOR ACADEMIC LIBRARIES - Channankegowda (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Open Access (OA) resources have transformed the landscape of academic libraries by offering unrestricted access to scholarly information. This study delves into the challenges and opportunities that open access presents for academic libraries. It highlights the role of OA in promoting equitable access to information, reducing the cost of scholarly communication, and enhancing global collaboration. The study also identifies challenges such as sustainability, copyright concerns, and technological barriers. Through a comprehensive analysis, the research provides actionable recommendations for academic libraries to effectively integrate and promote OA resources, ensuring their relevance in a rapidly evolving information environment.